2019
DOI: 10.1111/adb.12779
|View full text |Cite
|
Sign up to set email alerts
|

Dietary yeast influences ethanol sedation in Drosophila via serotonergic neuron function

Abstract: Abuse of alcohol is a major clinical problem with far‐reaching health consequences. Understanding the environmental and genetic factors that contribute to alcohol‐related behaviors is a potential gateway for developing novel therapeutic approaches for patients that abuse the drug. To this end, we have used Drosophila melanogaster as a model to investigate the effect of diet, an environmental factor, on ethanol sedation. Providing flies with diets high in yeast, a routinely used component of fly media, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 96 publications
(311 reference statements)
1
5
0
Order By: Relevance
“…To determine whether glial Tdc2 was altering alcohol sedation via a pharmacodynamic or pharmacokinetic mechanism, we measured alcohol levels in flies expressing Tdc2 RNAi via repo-Gal4 and control genotypes after prescribed periods of alcohol exposure. As expected, 31,32 internal alcohol levels significantly increased the longer flies were exposed to alcohol (Table S2, Time factor). Importantly, though, genotype did not affect internal alcohol levels (Genotype factor), indicating that constitutive pan-glial Tdc2 knockdown did not S2).…”
Section: Tdc2 Expression Within Glia Regulates Alcohol Sedation Throu...supporting
confidence: 79%
“…To determine whether glial Tdc2 was altering alcohol sedation via a pharmacodynamic or pharmacokinetic mechanism, we measured alcohol levels in flies expressing Tdc2 RNAi via repo-Gal4 and control genotypes after prescribed periods of alcohol exposure. As expected, 31,32 internal alcohol levels significantly increased the longer flies were exposed to alcohol (Table S2, Time factor). Importantly, though, genotype did not affect internal alcohol levels (Genotype factor), indicating that constitutive pan-glial Tdc2 knockdown did not S2).…”
Section: Tdc2 Expression Within Glia Regulates Alcohol Sedation Throu...supporting
confidence: 79%
“… 104 A recent study also found that 5-HT signaling in flies was required for dietary yeast-induced increases in alcohol consumption and resistance to sedation. 105 This study highlights the conserved link between 5-HT, diet, and alcohol-related behavior across species. It is interesting that both adrenergic and serotonergic transmission influence mammalian alcohol-associated behaviors as it was recently discovered that flies have a novel adrenergic-like receptor (DmOcta2R).…”
Section: Serotonin Receptorsmentioning
confidence: 67%
“…5HT may also be involved in the relationship between diet and ethanol sedation. In general, a high-yeast diet increases 5HT levels in the brain (Ro et al, 2016) and increases flies' resistance to alcohol sedation (Schmitt et al, 2020). Serotonergic neurons can block the sedation resistance caused by a high-yeast diet (Schmitt et al, 2020), suggesting a role for 5HT in mediating the link between diet and ethanol-related behaviors.…”
Section: Locomotion Sensitivity and Sedationmentioning
confidence: 99%